2019
DOI: 10.1093/gbe/evz142
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Survey on the Terpene Synthase Gene Family Provides New Insight into Its Evolutionary Patterns

Abstract: Terpenes are organic compounds and play important roles in plant growth and development as well as in mediating interactions of plants with the environment. Terpene synthases (TPSs) are the key enzymes responsible for the biosynthesis of terpenes. Although some species were employed for the genome-wide identification and characterization of the TPS family, limited information is available regarding the evolution, expansion, and retention mechanisms occurring in this gene family. We performed a genome-wide iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(107 citation statements)
references
References 84 publications
6
101
0
Order By: Relevance
“…Similar to the TPS-a group, the TPS-c group was further divided into dicot and monocot subclades. Consistent with a previous report, the TPS-d subfamily was specific to gymnosperms, and the TPS-h subfamily was only observed in S. moellendorffii [1,11,12,17], inferring that they might play a particular role in these species.…”
Section: Phylogenetic Analysis Of Dotps Genes In D Officinalesupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to the TPS-a group, the TPS-c group was further divided into dicot and monocot subclades. Consistent with a previous report, the TPS-d subfamily was specific to gymnosperms, and the TPS-h subfamily was only observed in S. moellendorffii [1,11,12,17], inferring that they might play a particular role in these species.…”
Section: Phylogenetic Analysis Of Dotps Genes In D Officinalesupporting
confidence: 91%
“…Another angiosperm-specific TPS-g encodes monoterpene synthase without the R(R)X 8 W motif. TPS-h is only observed in Selaginella moellendorffii [1,[9][10][11]. In addition, TPS harbors conserved structural features such as DDxxD, NSE/DTE, and R(R)X 8 W motifs [1].…”
Section: Introductionmentioning
confidence: 99%
“…However, motif 9 and 10 were only present in subfamilies III (a + c) and VII, respectively. Variation in conserved motifs permits the classification of proteins into subfamilies and reflects each subfamily's specific functions (Jiang et al, 2019). Gene structure can also provide information for the study of gene family evolution (Guo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple sequence alignment demonstrated that three DoGES proteins had highly conserved aspartate-rich motifs (DDxxD) and NSE/DTE motifs at the C -terminal, and an RRX 8 W domain at the N -terminal ( Figure 2 ), suggesting that DoGES1-3 were all TPSs. Among them, DDxxD and NSE/DTE were essential for the cofactor Mg 2+ or Mn 2+ to catalyze the synthesis of monoterpenes [ 18 , 19 ], and the RRX 8 W domain was also involved in the cyclization of monoterpene synthase [ 20 ].…”
Section: Resultsmentioning
confidence: 99%